Catalytic function of Drosophila melanogaster glutathione S-transferase DmGSTS1-1 (GST-2) in conjugation of lipid peroxidation end products. - Singh, S.P.; Coronella, J.A.; Benes, H.; Cochrane, B.J.; Zimniak, P. (European Journal of Biochemistry, 2001)
Drosophila melanogaster glutathione S-transferase DmGSTS1-1 (earlier designated as GST-2) is related to sigma class GSTs and was previously described as an indirect flight muscle-associated protein with no known catalytic properties. We now report that DmGSTS1-1 isolated from Drosophila or expressed in Escherichia coli is essentially inactive toward the commonly used synthetic substrate 1-chloro-2,4-dinitrobenzene (CDNB), but has relatively high glutathione-conjugating activity for 4-hydroxynonenal (4-HNE), an electrophilic aldehyde derived from lipid peroxidation. 4-HNE is thought to have signaling functions and, at higher concentrations, has been shown to be cytotoxic and involved in the etiology of various degenerative diseases. Drosophila strains carrying P-element insertions in the GstS1 gene have a reduced capacity for glutathione conjugation of 4-HNE. In flies with both, one, or none of the GstS1 alleles disrupted by P-element insertion, there is a linear correlation between DmGSTS1-1 protein content and 4-HNE-conjugating activity. This correlation indicates that in adult Drosophila 70 +/- 6% of the capacity to conjugate 4-HNE is attributable to DmGSTS1-1. The high abundance of DmGSTS1-1 (approximately 2% of the soluble protein in adult flies) and its previously reported localization in tissues that are either highly aerobic (indirect flight muscle) or especially sensitive to oxidative damage (neuronal tissue) suggest that the enzyme may have a protective role against deleterious effects of oxidative stress. Such function in insects would be analogous to that carried out in mammals by specialized alpha class glutathione S-transferases (e.g. GSTA4-4). The independent emergence of 4-HNE-conjugating activity in more than one branch of the glutathione S-transferase superfamily suggests that 4-HNE catabolism may be essential for aerobic life.